Perancangan Sistem Kartu Identitas Berobat Menggunakan Metode Waterfall - Faujia, Sheny; Syahidin, Yuda; Elvira, Shinta (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The rapid development of technology affects many fields, one of which is the health sector. In hospitals, technological developments are needed to perform outpatient, inpatient and emergency services. Behind the rapid development of technology, not a few hospitals still use manual systems. In Hospital X, for example, the use of a medical identity card (KIB) still uses paper / manual. Patients who come for treatment often forget to bring their treatment cards, cards are damaged and difficult to read, patient category stickers and treatment cards are lost. This makes it difficult for officers and hampers the service process. In this study, the main objective is to create an electronic medical identity card. The method used in this research is qualitative research with a descriptive approach, which focuses on the description and interpretation of data obtained from observations and interviews. In addition, the Waterfall method will be used to design an electronic medical identity card system. By making this electronic medical identity card, it is hoped that it can minimize and overcome existing problems in the service system, so that the quality of service provided can be further improved.